EFEKTIVITAS PENYALURAN DANA PROGRAM KELUARGA HARAPAN (PKH) DALAM UPAYA PENGENTASAN KEMISKINAN PADA PESERTA PKH DESA MUARA TIKU KEC.KARANG JAYA KABUPATEN MUSI RAWAS UTARA - Handika, Yuli; Desi Isnaini; Yunida Een Fryanti (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2023)
The purpose of this study was to find out how effective the distribution of the Family Hope Program (PKH) funds was and the obstacles in the process of channeling PKH funds in Muara Tiku Village, Karang Jaya District, North Musi Rawas Regency. In this study the authors used a qualitative descriptive research method through interviews, observation, and documentation with research locations in Muara Tiku Village, Karang Jaya District, North Musi Rawas Regency. The informants in this study were 60 informants (all). And what is the focus of the problem in this research is how the effectiveness of the Family Hope Program (PKH) in efforts to alleviate poverty after the Covid-19 pandemic with indicators of the effectiveness of program understanding, target accuracy, goal accuracy, goal achievement and real change. The results showed that the Family Hope Program (PKH) in Muara Tiku Village, Karang Jaya District, was not maximally effective. Where only 2 indicators are said to be effective, namely indicators of goal achievement and real change. Meanwhile, the other 3 indicators were not yet effective, namely indicators of program understanding, target accuracy, and timeliness. Then, the usual obstacle in the process of channeling the Family Hope Program (PKH) funds is the lack of meetings between beneficiaries and PKH assistants, the distance of the post office from the village, and the process of updating data takes a long time.